Nevroteologija med frenologijo in nevromitologijo - Kuran, Manuel (Časopis za kritiko znanosti, 2011)
The article discusses the scientific paradigm of neurotheology, i.e.research of neurophysiological base of religious experience. In the last decade, this type of research has been strongly present in (neuro)cognitive studying of religion as a complex biological,psychological and sociological phenomenon. Nevertheless, the status of neurotheology is paradoxical. On one hand, published surveys and studies regularly become bestsellers, but on the other, scientists from other fields of science (notably psychology, sociology and philosophy) criticise neurotheology for its unacceptable reductionism and label it a "new phrenology". The main part of the article therefore representsa comparison of theoretical and epistemological aspects of neurotheology to those of phrenology, a pseudoscientific discipline of the early 19th century. Key research studies and theoretical foundations of both disciplines are presented and in the final part, similarities and differences are discussed. The article is concluded with a critical reflection on the hegemonic status of the brain in modern (neuro) cognitive science, which has been dubbed by Tallis as "neuromythology". The purpose of the article is twofold. First, to critically evaluate the shift from pure speculation to experimental research of religion. Second, to highlight the similarities and differences between neurotheology and phrenology, thus assessing the plausibility of the term "new phrenology".
Keywords: religijsko doživljanje; religious experience; bog; neurotheology; nevroteologija; phrenology; neuromythology; frenologija; neurocognitive science; nevromitologija; nevrokognitivne znanosti; cognitive science; kognitivne znanosti; god